Transverse lie with prolapsed arm in a female red‐howler monkey (Alouatta guariba clamitans – Cabrera, 1940). Issue 3 (19th May 2016) - Daneze, Edmilson R.; Penna, Beatriz L.; Marcondes, Lucas F.; Léga‐Palazzo, Elzylene; Magalhães, Geórgia M.
Abstract: This study focuses on a case of a red‐howler monkey ( Alouatta guariba clamitans ) which was found with a fetus in a transverse lie position with a prolapsed arm. The topic of this research is well justified as there are no data on this condition involving this type of non‐human primate in literature. In this study, a red‐howler monkey was observed by locals pulling at her pelvic region for 3 days near a farm. On the third day, the monkey was found lying on the ground at which point she offered no resistance when approached. The environmental police took the monkey to receive medical attention. During the physical examination, it was quickly observed that the monkey was pregnant; the right forelimb of the fetus was exposed from the vulva. An ultrasound revealed a non‐viable fetus, and due to the severe weakness of the mother, we opted for euthanasia. During the necropsy, not only was the fetus found macerated but it was also in a transverse lie position with a prolapsed arm and presented no external or internal injuries consistent with trauma.